Building Professional Competence of Prison Staff: Psychological, Pedagogical, and Legal Aspects - Anishchenko, Viktoriia; Sharapova, Yuliia; Leonenko, Oleksii; Sorokopud, Viacheslav; Kyriienko, Andrii (International Journal of Statistics in Medical Research, 2024)
Considering the war in Ukraine, the study of the main aspects of building the professional competence of the prison staff is a current priority task of the State Penitentiary Service of Ukraine. The objective of the study is to determine the components of professional competence of the prison staff in Ukraine. Methods. The Social Readjustment Rating Scale, the Bass Personality Orientation Test, and the Coping Strategy Indicator (CSI). Statistical analysis involves the use of descriptive statistics and correlation analysis. Results. Graduates of the penitentiary system have formed general and special professional competencies, including partial stress resistance, coping with problem solving, and motivational focus on the task. It has been proven that general professional competencies are directly related to professionally important qualities (р≤0.01). Conclusions. The results can be used by higher education institutions (HEIs) to adjust professional training programs for prison staff. Heads of penal institutions can consider the obtained results when selecting staff for positions. The results are useful for the professional self-development of specialists, as they indicate the qualities and competencies that they need to develop. Prospects. Further study may focus on determining how the professional competencies of the prison staff are built at different stages of their professional activities.